2014
DOI: 10.1111/hsc.12142
|View full text |Cite
|
Sign up to set email alerts
|

How older people cope with frailty within the context of transition care in Australia: implications for improving service delivery

Abstract: Transition care is increasingly common for older people, yet little is known about the subjective experience of the transition care 'journey' from the perspective of clients themselves. This study examines how older people cope with frailty within the context of a dedicated transition care programme and discusses implications for improving service delivery. Qualitative in-depth interviews were carried out during 2011 in the homes of 20 older people who had recently been discharged from a transition care progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 30 publications
(37 reference statements)
2
29
0
7
Order By: Relevance
“…Twentysix papers contributed to this theme [3136,3840,43,46,47,5258,60,62,65,7072,74]. This theme presents findings related to care providers’ capacity to care, taking a patient-centred and family-centred approach to care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twentysix papers contributed to this theme [3136,3840,43,46,47,5258,60,62,65,7072,74]. This theme presents findings related to care providers’ capacity to care, taking a patient-centred and family-centred approach to care.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies illustrate examples of older people and their carers refusing services offered [15], or expressing reluctance to seek care even whilst acknowledging that such support is needed [16]. There are also indications that dependency on services, but limited participation in decision making, can produce feelings of devaluation and disempowerment in older persons [17]. It is essential to take into account older adults’ views, attitudes and understandings related to their own coping and care planning strategies, and to care and interventions in the context of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta‐synthesis review, user experience of transitional care was a social process of negotiation and navigation of independence for older people and carers . Other research has also found that independence is important to older people living in the community both with and without support . The current finding contributes to our understanding that ideal transitional care interventions should focus on patients’ desire and need to regain independence as well as on communication between practitioners about the discharge assessment and plan of care; preparation of the person and carer for the care transition; reconciliation of medications at transition; a plan for follow‐up care; and patient education about self‐management …”
Section: Discussionmentioning
confidence: 67%
“…Fragmentation of service delivery, lack of control of the client over the services delivered, and uncertainty about future support were identified as the issues whose resolution would increase benefits from the program. 43 In part, the difficulties of transition relate to the availability of residential aged care. Podger, writing in 2006, pointed to about 2,000 elderly people in hospital awaiting residential aged care.…”
Section: Aging and The Australian Hospital Systemmentioning
confidence: 99%